Ocular prosthetic of patient with shallow socket: Different impression technique - Putri, Nadya K.; Adella S. Maharani; Murti Indrastuti; Sri B. Barunawati (Indonesian Journal of Prosthodontic, 2025)
ABSTRACT The loss of an eyeball can be caused by trauma, surgery, or defects in the ocular area. Missing this part of the body can result in loss of vision and a decrease in self-confidence for the patient. Through our clinical report, a custom-made ocular prosthesis was made using acrylic resin materials which aims to provide rehabilitative care and restore patient self-confidence. A 27-year-old patient came to RSGM Prof. Soedomo for an ocular prosthesis after losing her eyeball due to an infection. Clinical examination revealed that the patient's ocular profile is convex while her eye sockets are shallow. This makes it challenging to create an ocular prosthesis. In this case report, the impression of work model uses two methods to determine the best way to make an impression of shallow eye sockets. Using an individual tray, one impression uses putty and light body, and the other uses light body only. Better results were obtained when the impression was made using the light body only in this case. The patient expressed satisfaction with her new custom-made ocular prosthetic. When compared to manufactured ocular prosthesis, custom-made prostheses offer superior fitting, comfort, and aesthetics, as they closely resemble the contralateral patient's natural eye. Keywords: Ocular prosthesis, Shallow eye socket, Impression technique.